2018
DOI: 10.3390/s18113990
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stainless Needle Electrodes and Silver Disk Electrodes over the Interhemispheric Cerebral Coherence Value in Vigil Dogs

Abstract: Electroencephalography (EEG) is an objective diagnostic tool in the evaluation of cerebral functionality, both in human and veterinary medicine. For EEG acquisition, different types of electrodes are used, as long as they have no impact on the recorded background activity. However, to date, the influence of electrode type on quantitative EEG and cerebral coherence has not been investigated. Twenty EEG traces (ten with needle electrodes and ten with disk electrodes) were recorded from ten mesocephalic vigil dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“… 18 Ambulatory EEG was recorded using current standard minimally invasive SC (needle or wire) electrodes. 19 , 20 The duration of AEEG recordings was not standardized for various reasons, including dogs removing electrodes during the recording, sufficient episodes of interest obtained, or time of hospital discharge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 Ambulatory EEG was recorded using current standard minimally invasive SC (needle or wire) electrodes. 19 , 20 The duration of AEEG recordings was not standardized for various reasons, including dogs removing electrodes during the recording, sufficient episodes of interest obtained, or time of hospital discharge.…”
Section: Methodsmentioning
confidence: 99%
“…Wireless AEEG with synchronized video was recorded using a Trackit MK3 AEEG/Polygraphy recorder (Lifelines Neurodiagnostic Systems, Troy, Illinois), with scalp EEG using 13 channels (both hemispheres symmetrically in the frontal [F3, F4, F7, F8], parietal [C3, C4], temporal [T3, T4] and occipital [O1, O2] regions and 3 midline anterior‐posterior locations [Fz, Cz, Pz]) in addition to a reference electrode (between the medial canthi) and a ground electrode (dorsal cervical midline, 2‐5 cm caudal to the nuchal crest) 18 . Ambulatory EEG was recorded using current standard minimally invasive SC (needle or wire) electrodes 19,20 . The duration of AEEG recordings was not standardized for various reasons, including dogs removing electrodes during the recording, sufficient episodes of interest obtained, or time of hospital discharge.…”
Section: Methodsmentioning
confidence: 99%
“…One of the main reasons could be that in our previous study we used needle electrodes that have a much smaller recording surface than the cup electrodes. In fact, Musteata et al found that values of interhemispheric coherence in dogs are dependent on the type of electrode used (94). A limitation of coherence analyses is that coherence values can be overestimated due to volume conduction in which the conductive properties of the brain, cerebrospinal fluid, skull, and scalp (and the conductive gel used during the recording), cause the neural source information to diffuse before reaching the electrodes (95, 96).…”
Section: Interhemispheric Coherence and Cognitionmentioning
confidence: 99%
“…As a consequence, removing the DC component of the input signal is a necessary stage when low-voltage signals are acquired. Especially in the case of neurophysiological monitoring, adhesive or needle electrodes are connected to the subject being monitored [14][15][16]; the half cell potential of the two electrodes between which the measurement is carried out are never exactly the same, causing an inherent differential voltage in the contact circuit. This results in a DC offset in the input signal that has to be removed [17,18].…”
Section: Introductionmentioning
confidence: 99%